DEVELOPING A MODEL OF DISCOURSAL STORIES FOR CHILDREN IN THE CONCRETE OPERATIONAL PHASE - Syarifah, Ety; Rustono, Rustono; J.Waluyo, Herman; Zulaeha, Ida (Universitas Negeri Semarang, 2017)
This study is meant to develop a model of discoursal stories for children suitable with their development or age level as readers. The discoursal stories are developed by considering suitable characteristics of learners as readers, teacher’s needs for learning media, and learners’ reading interest. To develop the model as learning media for Grade IV, a research and development method with three stages: (1) preliminary study, (2) product formulation and development, and (3) product validation and dissemination were used. There are two types of results in this research: criteria for the model of children’s discoursal stories in their concrete operational phase and the development of the discourse model. The model has the theme of friendship, humanity/social issues, and education, with joy and playful tone, joyful, moving /pityful/compassionate and relaxed athmosphere. Learners need to feel happy, moving, and patient, and like human being, inanimate and animate objects as main characters. The diction should be plain and metaphorical. The stories should be presented by considering the book format, fonts, paper color variety, font size, and various pictures. The language should be communicative. The content of the children’s poetry should be useful and understandable. The scene technique should be used as the method of presentation with dialogues or description. Learners like human being as the characters, completed with clear setting, linear plots, with friendship as the theme.